الأحكام العامة لحق الحكر في التذريع الج ا زئري - قدوري, ثورية (جامعة الوادي -University eloued, 2021)
حق الحكر مف المعاملات القديمة التي نص عمييا الفقو الإسلامي كيرجع كجكد الحكر في البمداف الإسلامية إلى منتصف القرف الثالث ىجرؼ, كقد ظير بسبب حاجة الناس إلى ىذه المعاممة, كالحكر مرتبط بالكقف, كلذلؾ تناكؿ أحكامو الفقياء عند حديثيـ عف الكقف, كانتقل بعد ذلؾ إلى القكانيف الكضعية في الدكؿ الإسلامية كمف بينيا الجزائر, حيث رقـ نص عميو القانكف 07/01المؤرخ في 22مايك 2001المعدؿ كالمتمـ لمقانكف رقـ 10/91المؤرخ في 27أبريل 1991كالمتعمق بالأكقاؼ, كاعتبره المشرع الج ا زئرؼ مف طرؽ استغلاؿ كاستثمار العقارات الكقفية, كحاكؿ تعريفو العديد مف الفقياء كالباحثيف كمع ذلؾ مازاؿ الحكر مف المفاىيـ الفقيية كالقانكنية الغامضة, كغير معركؼ عند الكثير مفThe right of the hikr is one of the ancient transactions stipulated by Islamic jurisprudence. The presence of the hikr in Islamic countries dates back to the middle of the third century AH. Then he moved to the man-made laws in Islamic countries, including Algeria, where Law No. 01/07 of May 22, 2001 amending and supplementing Law No. 91/10 of April 27, 1991 related to endowments, stipulated it, and the Algerian legislator considered it a way of exploiting and investing endowment properties, Many jurists and researchers have tried to define it, however, the hikr is still one of the ambiguous jurisprudential and legal concepts, and it is unknown to many legal specialists, and it is still difficult to distinguish between it and many other transactions that are similar to it. It seems that the Algerian legislator was influenced by this opinion and this appears in the French text of Article 26 bis 2 of the Endowments Law, in which the legislator translated the word “hikr” المختصيف في القانكف, كلا ي ا زؿ يصعب التمييز بينو كبيف العديد مف المعاملات الأخرػ التي تشبيو, كيبدك أف المشرع الج ا زئرؼ قد تأثر بيذا الرأؼ كيظير ذلؾ في النص الفرنسي
Keywords: الأحكام العامة، لحق الحكر في التشريع ،الجزائري; General provisions, right of monopoly In Legislation, Algerian